(3efgGL GdYGQa GdefJbi heYQGL GdSGdc GdeQJbis - (3YHO GdbGOQ GdcjdGfjs ((3ESeGYjd Hf eMeO GdTGT s)
(3ChdgG (B:s
(3QH jSQ CeG HYO aEf GdCSHGH GdJi jJbQH HgG Zdi Gddg JYGdi KdGKI (B: (3EYJbGO hYde hYed fXeJ gPg GdbUjOI hbO SejJgG efgGL GdYGQa GdefJbi heYQGL GdSGdc GdeQJbi s
(3BNQgG (B:s
(3hdi hdNjQ Gddg CLeY CHJZi ef Gdgd QVhGfkG hYhfkG Je cJGH efgGL GdYGQa GdefJbi heYQGL GdSGdc GdeQJbi HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3oaUdJ CHhGHg HGdeOGO GdCMeQs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs